2022
DOI: 10.3390/app12147021
|View full text |Cite
|
Sign up to set email alerts
|

Complex Band Structure of 2D Piezoelectric Local Resonant Phononic Crystal with Finite Out-Of Plane Extension

Abstract: In this study, a new type of 2D piezoelectric phononic crystal with a square hollow and convex structures is designed and established. A theoretical study of the piezoelectric phononic crystal is presented in this article to investigate the transmission properties of waves in terms of complex dispersion relations. Based on the finite discretization technique and plane wave expansion, the formula derivation of the real band structure is achieved as well as the complex band diagrams are obtained. The numerical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The bandgap can be regulated by changing the external voltage or circuit using the piezoelectric effect of piezoelectric materials. Miao et al [12] constructed a square 2D piezoelectric PC structure with a hollow outer convexity. They compared the transmission loss results with and without an external circuit, laying the foundation for active control of piezoelectric PC structures.…”
Section: Introductionmentioning
confidence: 99%
“…The bandgap can be regulated by changing the external voltage or circuit using the piezoelectric effect of piezoelectric materials. Miao et al [12] constructed a square 2D piezoelectric PC structure with a hollow outer convexity. They compared the transmission loss results with and without an external circuit, laying the foundation for active control of piezoelectric PC structures.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [25] used a PWE method, based on the Mindlin piezoelectric plate theory, to derive the dispersion relation of bending waves in a nonuniform piezoelectric plate. Miao and his co-workers [26] implemented the derivation of the formulae for the energy band structures based on the finite element method and the plane wave expansion method. They obtained the energy band diagrams of the corresponding piezoelectric structures.…”
Section: Introductionmentioning
confidence: 99%
“…Among these intriguing functionalities, the band gaps, appearing as a result of the wave motion in such composites, have gained increasing attention for reducing vibration and sound [ 1 , 2 , 3 , 4 ] since the elastic and acoustic waves are forbidden from propagating through the frequency regions inside the band gaps. Using different types of mechanisms, Bragg band gaps [ 5 , 6 ], local resonance gaps [ 7 , 8 , 9 ] and inertial induced gaps [ 10 , 11 ] were investigated to satisfy various structural requirements of applications in vibration and noise control. Numerous studies [ 12 , 13 , 14 ] have demonstrated that structural configuration and material properties play a significant role in determining wave propagation and attenuation performance regardless of whether underlying mechanisms are used.…”
Section: Introductionmentioning
confidence: 99%